Effect of estrogen administration on middle cerebral arterial viscoelastic properties in aged female rats - Qin,Zhigang (2016)
ABSTRACT PURPOSE: To develop a model for studying cerebrovascular disease prevention in elderly women. METHODS: Sixty 18-month-old Sprague Dawley (SD) rats were randomly divided into an estrogen administration group (EA, n=30) and a non-administration group (NA, n=30); thirty 4-month-old SD rats were allocated to a control group. The EA group received estradiol benzoate starting on the 5th day of a 34-day breeding period, and the serum levels of estradiol (E2), estrogen receptor (ER), and malondialdehyde (MDA) were measured. The MCA of each group was then sampled for viscoelastic experiments. RESULTS: The serum levels of E2 and MDA in the EA group showed significant differences compared to those in the control group (p<0.05), while the difference in ER between the EA and control groups was not significant (p>0.05). The decrease in MCA stress at 7,200 s and the increase in strain at 7,200 s in the EA group showed no significant differences compared to the control group (p>0.05). CONCLUSION: Estradiol administration inhibited the formation of lipid peroxidation products and restored middle cerebral arterial viscoelasticity in aged female rats.